Community Structure of Fishes at Coral Reef Ecosystem in Pandanan Beach, Northern Lombok, West Nusa Tenggara - Irawan, Muhammad Rizki Putra; Candri, Dining Aidil; Zamroni, Yuliadi (Jurnal Biologi Tropis, 2024)
One of the most abundant kinds of organism that lived in coral reef ecosystem are fish. Fish rely on coral reefs for shelter, food, and breeding grounds. Lombok is one of the islands that have many hotspots of coral reef ecosystem, one of which is at Pandanan Beach. The precense of fish benefits in both tourism and local economy, however the data about reef fish that lived in Pandanan waters are less known. This research aimed to assess the community structure of fish species in coral reef ecosystem at Pandanan Beach. The method that was used for sampling were UVC (Underwater Visual Census) with BIT (Belt Intercept Transect) technique at three different stations. The results showed 554 individuals which consist of 34 species from 12 families had been identified. The community structure of fish in the three stations showed the moderate level of diversity, stable evenness index with low dominance, and density value of 0,73. Environmental parameters measurement indicate Pandanan waters are suitable for fish growth and survival.